1965
DOI: 10.1530/jrf.0.0090189
|View full text |Cite
|
Sign up to set email alerts
|

Sialic Acid in Semen, Spermatozoa and Serum of Mammals

Abstract: Summary. A comparative study of the sialic acid content of semen, serum and spermatozoa from several mammalian species was made.The sialic acid content of semen showed a very wide range of concentration in the four species examined, while the sialic acid concentrations in serum were much more uniform. The semen from man and bull contained higher concentrations of sialic acid than the serum of these respective species. The reverse was found in rabbit and dog.Only a small fraction of the total sialic acid in sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1970
1970
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It is known that both blood and seminal plasma contain sialic acid and the levels are higher in semen compared to blood [ 66 ]. However, this is the first study to show that the sialic acid signature of body fluids is preserved in their EVs.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that both blood and seminal plasma contain sialic acid and the levels are higher in semen compared to blood [ 66 ]. However, this is the first study to show that the sialic acid signature of body fluids is preserved in their EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sialic acid may play an important role in the process of fertilization [19]. Several authors reported the sialic acid content in human sperm [ 10,11,161. These authors used the washed sperm prepared by centrifugation of the diluted semen.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the fact that both human sperm and seminal plasma possess sialic acids (Svenerholm 1958;Warren 1959;Hudson et al 1965;Levinsky et al 1983a,b), the likely occurrence of sialoglycoproteins on the surface of human sperm and in human seminal plasma is anticipated. Since certain of the sialoglycoproteins cited above are involved in sperm maturation, motility or capacitation, we considered it worthwhile to identify the sialoglycoproteins in human ejaculated sperm and seminal plasma.…”
mentioning
confidence: 99%